SCARECROW, SCR‐LIKE 23 and SHORT‐ROOT control bundle sheath cell fate and function in Arabidopsis thaliana. (26th March 2014) - Cui, Hongchang; Kong, Danyu; Liu, Xiuwen; Hao, Yueling
Summary Bundle sheath (BS) cells form a single cell layer surrounding the vascular tissue in leaves. In C3 plants, photosynthesis occurs in both the BS and mesophyll cells, but the BS cells are the major sites of photosynthesis in C4 plants, whereas the mesophyll cells are only involved in CO2 fixation. Because C4 plants are more efficient photosynthetically, introduction of the C4 mechanism into C3 plants is considered a key strategy to improve crop yield. One prerequisite for such C3‐to‐C4 engineering is the ability to manipulate the number and physiology of the BS cells, but the molecular basis of BS cell‐fate specification remains unclear. Here we report that mutations in three GRAS family transcription factors, SHORT‐ROOT (SHR), SCARECROW (SCR) and SCARECROW‐LIKE 23 (SCL23), affect BS cell fate in Arabidopsis thaliana. SCR and SCL23 are expressed specifically in the BS cells and act redundantly in BS cell‐fate specification, but their expression pattern and function diverge at later stages of leaf development. Using ChIP–chip experiments and sugar assays, we show that SCR is primarily involved in sugar transport whereas SCL23 functions in mineral transport. SHR is also essential for BS cell‐fate specification, but it is expressed in the central vascular tissue. However, the SHR protein moves into the BS cells, where it directly regulates SCR and SCL23 expression. SHR, SCR and SCL23 homologs are present in many plant species, suggesting that this developmental pathway for BS cell‐fate specification is likely to be evolutionarily conserved.